Constructing an Attitude Scale Toward Family Planning Using the General Graded Unfolding Model - Bani Ata, Zaid (Jordan Journal of Educational Sciences, 2008)
This study aimed at using the General Graded Unfolding Model for constructing an attitude scale toward family planning. To achieve the purpose of the study a preliminary Likert rating scale of 50 items was constructed.The scale was administrated to a randomly selected sample of 1200 parents. The results indicated 41 items met the expectations of the model and their scale value cover the latent continuum and they have suitable psychometric properties with a reliability coefficient 0.93,and they also have several validity indicators. The results also showed that the items of the scale have high discrimination. This made them contribute in offering the maximum amount of the information within the range of items vale scale. So,they consist with the model expectations